PENGARUH MEDIA QUESTION CARD TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V UPT SD NEGERI 101906 PAGAR JATI - Enjelika Sinaga; Lisbet Novianti Sihombing; Hetdy Sitio (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of Question Card media on Student Learning Outcomes in the Science Subject of Class V of UPT SD Negeri 101906 Pagar Jati. This study uses a quantitative research method with